Design and Construction of a UV-C Sterilization System Using the Arduino System - Abd AL-Qader Mohammed Faris (Scholars Digest Publishing, 2023)
UV-C defines the ultraviolet radiation with wavelength range of 280 to 100 nanometres. Most people have heard of the dangers of UV-A (400 – 315 nm) and UV-B (315 - 280 nm) exposure from the sun or from sunbeds. UV-C is also produced by the sun, but it is the shortest of the ultraviolet wavelengths and is almost entirely filtered out by the atmosphere before reaching the earth’s surface. Therefore, people have little or no natural exposure to it, and that’s a good thing. The shorter the wavelength, the more impact ultraviolet radiation could have on human health. For this research, the working principle of the uv sterilizer, uv sterilizer set of optical, microbiology, machinery, electronics, fluid mechanics, such as designed on the basis of the principle of comprehensive science, with high efficiency, high strength and high life water strong uv ultraviolet germicidal lamps, when the bacteria, viruses and other water after uv irradiation.
Keywords: based Sterilization, UV-C Radiation, bacteria, Arduino, Reed Switch (NO).